Identification of B-KSR1, a Novel Brain-Specific Isoform of KSR1 That Functions in Neuronal Signaling - Müller, Jürgen (American Society for Microbiology, 2000)
Kinase suppressor of Ras (KSR) is an evolutionarily conserved component of Ras-dependent signaling pathways. Here, we report the identification of B-KSR1, a novel splice variant of murine KSR1 that is highly expressed in brain-derived tissues. B-KSR1 protein is detectable in mouse brain throughout embryogenesis, is most abundant in adult forebrain neurons, and is complexed with activated mitogen-activated protein kinase (MAPK) and MEK in brain tissues. Expression of B-KSR1 in PC12 cells resulted in accelerated nerve growth factor (NGF)-induced neuronal differentiation and detectable epidermal growth factor (EGF)-induced neurite outgrowth. Sustained MAPK activity was observed in cells stimulated with either NGF or EGF, and all effects on neurite outgrowth could be blocked by the MEK inhibitor PD98059. In B-KSR1-expressing cells, the MAPK–B-KSR1 interaction was inducible and correlated with MAPK activation, while the MEK–B-KSR1 interaction was constitutive. Further examination of the MEK–B-KSR1 interaction revealed that all genetically identified loss-of-function mutations in the catalytic domain severely diminished MEK binding. Moreover, B-KSR1 mutants defective in MEK binding were unable to augment neurite outgrowth. Together, these findings demonstrate the functional importance of MEK binding and indicate that B-KSR1 may function to transduce Ras-dependent signals that are required for neuronal differentiation or that are involved in the normal functioning of the mature central nervous system.